Evaluation of Surface Quality and Productivity in Conventional Milling of Copper Beryllium Using Minimum Quantity Lubrication - N. Mwangi, Ken; Wambua, Job; M. Mwema, Fredrick; M. Wakiru, James; Jen, Tien-Chien (Tribology in industry, 2024)
Copper Beryllium (C17200) has ideal physical and mechanical properties of high fatigue strength, thermal conductivity, and hardness, making the alloy ideal for various high-reliability applications in aerospace, producing inserts and tooling for hazardous environments. However, surface quality and productivity challenges are prominent when processing the alloy due to its properties. This study evaluates the surface quality and productivity in end-milling of Copper Beryllium by analyzing the effects of feed rate, minimum quantity lubrication (MQL) flow rate, and cutting depth on surface roughness (Ra) and material removal rate (MRR). The experiment was designed using the Box-Behnken design, and the samples were machined on a CNC milling machine. The results showed that the MQL flow rate was significant to surface roughness, while the cutting depth was significant to MRR. The optimum parameters were determined as a feed rate of – 60 mm/min, an MQL flow rate of – 80 ml/hr., and a cutting depth of – 0.511 mm, which yielded a surface roughness of 0.12 µm and MRR of 10.19 g/min. The study's novelty is that it considers MQL flow using vegetable oil-based cutting fluid (CF) as an input parameter in machining, offering insight into eco-friendly and cost-effective machining practices. Finally, the significance of the study lies in investigating the machinability of Cu-Be alloy material, addressing challenges related to surface quality and productivity during milling operation.